Cuprous oxide microspheres on graphene nanosheets: an enhanced material for non-enzymatic electrochemical detection of H2O2 and glucose. Issue 44 (16th May 2015) - Ding, Junwei; Sun, Wei; Wei, Gang; Su, Zhiqiang
<x xml:space="preserve">Abstract</x> Reduced graphene oxide nanosheets decorated with cuprous oxide microspheres show improved performances as a novel electrochemical sensor material.